Understanding the changing media landscape for promotion of Herbal Products and the impact of alternative sales channels on consumption - Rodosee, Fyruz Mahjuba (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.